Alkaline Chemistry and Applications - Marzouki, Riadh (IntechOpen, 2022)
Alkaline elements are present in large quantities and in different forms in the Earth's layers. They are widely used in the manufacture of materials showing interesting physical properties that can be applied in several fields, including catalysis, biology, energy, and others. This book describes different methods of synthesis and treatment of certain alkaline materials and their applications in different fields. It discusses alkaline chemistry in catalysis, biology, polymers and composites, and crystallography.